The Impact and Mechanism of a Novel Allosteric AMPA Receptor Modulator LCX001 on Protection Against Respiratory Depression in Rodents - Dai, Wei; Gao, Xiang; Xiao, Dian; Li, Yu-Lei; Zhou, Xin-Bo; Yong, Zheng; Su, Rui-Bin (Frontiers in Pharmacology, 2019)
Analgesics and sedative hypnotics in clinical use often give rise to significant side effects, particularly respiratory depression. For emergency use, specific antagonists are currently administered to counteract respiratory depression. However, antagonists are often short-lasting and eliminate drug generated analgesia. To resolve this issue, novel positive AMPA modulators, LCX001, was tested to alleviate respiratory depression triggered by different drugs. The acetic acid writhing and hot-plate test were conducted to evaluate analgesic effect of LCX001. Binding assay, whole-cell recording, live cell imaging, and Ca2+ imaging were used to clarify mechanism and impact of LCX001 on respiratory protection. Results showed that LCX001 effectively rescued and prevented opioid (fentanyl and TH-030418), propofol, and pentobarbital-induced respiratory depression by strengthening respiratory frequency and minute ventilation. The acetic acid writhing test and hot-plate test revealed potent anti-nociceptive efficacy of LCX001, in contrast to other typical ampakines that did not affect analgesia. Furthermore, LCX001 potentiated [3H]AMPA and L-glutamate binding affinity to AMPA receptors, and facilitated glutamate-evoked inward currents in HEK293 cells stably expressing GluA2(R). LCX001 had a typical positive modulatory impact on AMPAR-mediated function. Importantly, application of LCX001 generated a significant increase in GluA2(R) surface expression, and restrained opioid-induced abnormal intracellular Ca2+ load, which might participate in breathing modulation. Our study improves therapeutic interventions for the treatment of drug induced respiratory depression, and increases understanding of potential mechanism of AMPA receptor modulators.